Memories of Lincoln and the splintering of American political thought - Parry-Giles, Shawn J., 1960-; Kaufer, David S. (Rhetoric and democratic deliberation, 2017)
"Explores how memories of Lincoln became an important form of political rhetoric, and how divergent schools of U.S. political thought came to recruit Lincoln as their standard-bearer"--Provided by publisher